Firm-initiated stock trading suspension during a market crash - Huang, Jennifer; Shi, Donghui; Song, Zhongzhi; Zhao, Bin (Journal of Banking & Finance, 2025)
We investigate the determinants and effects of firm-initiated trading suspension during the Chinese stock market crash in July 2015. Our findings reveal that firms implemented suspensions to prevent investors’ panic selling, mitigate negative economic feedback, and safeguard specific shareholders’ interests. Once trading resumes, suspended stocks quickly align with the returns of comparable stocks, indicating that investors do not appear to penalize these firms in terms of valuation. Regarding post-resumption trading profits, small individual investors and institutions experience losses, whereas large individual investors and state agencies realize gains.